The Nexus of Corporate Social Responsibility and Consumer Perception : Systematic Review of the Evidence - Shetty, Swapna; Chaudhuri, Molly Sanjay; Shetty, Ankitha (Indian Journal of Marketing, 2022)
This paper aimed to facilitate researchers, academicians, and entrepreneurs to gain insights into the Asian consumer perspectives on corporate social responsibility (CSR) and its future research opportunities. The modus operandi for management review prescribed by Tranfield et al. (2003) was adopted for the present study. Since most research in this area originated from Western countries, it was pertinent to grasp the view of the consumers from the emerging economies in Asiatic countries. Further, PICO and PRISMA guidelines were considered for screening the research articles between 2010 and 2021 conducted in the Asian region. A total of 56 research papers were finalized for the study. It was found that the studies from the Asian region focused on empirical research, primarily conducted in BFSI and hospitality sectors. The orientation of people from the countries of the Asiatic region varied based on cultural and religious factors.